Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Proteomic insight reveals elevated levels of albumin in circulating immunecomplexes in diabetic plasma - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Patil, Yugendra R.; Shaikh, Mahemud L.; Regin, Bhaskaran S.; Mohan, Viswanathan; Giri, Ashok P.; Balasubramanyam, Muthuswamy; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2016)
A Hyperglycemic condition in diabetes promotes formation of advanced glycation end products, which are known to elicit immune response and form complexes with immunoglobulins called circulating immune complexes. To investigate the involvement of advanced glycation end product (AGE)-modified proteins in the elicitation of an immune response, circulating immune complexes were isolated and proteins associated were identified and characterized. Label-free-based mass spectrometric analysis of circulating immune complexes in clinical plasma of prediabetic, newly diagnosed diabetes, and diabetic microalbuminurea revealed elevated levels of serum albumin in the circulating immune complexes, which were also observed to be AGE modified. Further, to examine the role of glycation, circulating immune complexeswere analyzed in the streptozotocin-induced diabetic mice treated with or without aminoguanidine, a prototype glycation inhibitor. Mass spectrometric analysis of circulating immune complexes showed elevated levels of serum albumin in plasma from diabetic mice over that of control animals. Aminoguanidine-treated diabetic mice displayed decreased AGE modification of plasma albumin, accompanied by a reduced level of albumin in the circulating immune complexes. In addition, elevated levels of proinflammatory cytokines such as IL-1b, IL-2, and TNF-alpha were observed in diabetes, which were reduced with aminoguanidine treatment, suggesting the involvement of glycation in the immune response.